ANALYSIS OF THE INFLUENCE OF PARENTING PATTERNS ON THE INCIDENT OF STUNTING IN TODDLERS AGES (0-60 MONTHS)/ A LITERATURE REVIEW - Salydin, Oky Oktaviani; Tosepu, Ramadhan (Universitas Halu Oleo, 2024)
Abstract Stunting is a description of prolonged malnutrition during the most critical period of growth and development early in life. This can be interpreted as a toddler aged 0-59 months who has a height for age < -2 standard deviations and < -3 standard deviations from the median toddler growth standard set by WHO (UNICEF, 2013). Based on existing studies, the incidence of stunting, especially among toddlers, increases every year, therefore one of the current focuses of the Indonesian government is handling stunting. This research uses a literature review approach with the data source coming from indexed journal literature that has an ISSN (International Standard Serial Number) electronically which has been published via the internet from Google Scholar. The research data population is journals that focus on the incidence of stunting in toddlers aged 0-60 months in Indonesia, there are 15 indexed journals from various publishers or journal publishers. The search was limited by year of publication: namely from 2019-2022, namely the last 4 years of the writing of this research. Results: Fifteen (15) journals included in the literature review discuss different topics from the research that has been conducted, including discussing: 1) Education on parenting patterns, 2) The relationship between parenting patterns and the nutritional status of toddlers, and 3) The influence of parenting patterns. feeding on the incidence of stunting, 4) Description of children's food parenting patterns, 5) Nutritional parenting patterns. Keywords: Stunting, Toddler Age (0-60 Months), Parenting